Effect of Preoperative Nutritional Risk Screening on Postoperative Recovery in Patients with Laparoscopic-Assisted Radical Resection for Colorectal Cancer - Xiaolong Wang; Jianlin Wu; Sen Lei; Feng Tian; Ce Cao; Guangfeng Shi (Gastroenterology Research and Practice)
Background and Objectives. This study investigated the effect of preoperative nutrition on the recovery and prognosis of colorectal cancer patients after laparoscopic radical resection. Methods and Study Design. A retrospective analysis was conducted on 120 colorectal cancer patients between January 2015 and August 2017. Patients were divided into two groups: those without nutritional risk (NRS 2002<3) and those with nutritional risk (NRS 2002≥3). The impacts of preoperative nutritional status on postoperative complications and short-term outcomes were analyzed. Finally, univariate and multivariate logistic regression analyses were used to study risk factors associated with postoperative complications. Results. There were statistically significant differences in BMI, albumin, total cholesterol, and lymphocyte count between patients from the two groups (all P<0.05). There was no difference in the incidence rate of postoperative complications between the two groups, but there was a statistically significant difference in the total number of complications (P<0.05). There were no significant differences between the two groups regarding abdominal drainage volume, exhaust (flatus) time, hospitalization cost, morbidity, or 60 d readmission rate (all P>0.05). However, patients with nutritional risk had higher postoperative blood transfusion volumes, albumin infusions, weight difference before and after surgery, and postoperative hospital stays than the nonnutritional risk group (all P<0.05). Smoking, diabetes, and preoperative nutritional risk were the risk factors by the univariate and multivariate logistic regression analyses. Conclusions. The postoperative complication rate was increased, and the short-term efficacy was decreased in the preoperative nutritional risk group compared with those without nutritional risk.